A Changing Cityscape in Central Italy: The Gabii Project Excavations, 2012–2018. (3rd April 2021) - Samuels, J. Troy; Naglak, Matthew; Opitz, Rachel; Marilyn Evans, J.; Johnston, Andrew C.; Wright, Parrish; Creola, Alexandra; Prosser, James; Zapelloni-Pavia, Arianna; Farr, Jason; Harder, Matt; Banducci, Laura; et al.
ABSTRACT: Excavations carried out at the Latin city of Gabii between 2012 and 2018 have contributed new data to a number of debates around the emergence, lived experience, maintenance, decline, and resilience of cities. Gabii's urban trajectories demonstrate both seemingly familiar forms of urbanism and, on closer study, many locally circumscribed elements. Specifically, the Gabii Project excavations have uncovered an early Iron Age (8th–5th centuries b.c. ) hut complex that has provided evidence for architecture, funerary rites, and quotidian activities during the initial polynuclear settlement at urbanizing Gabii. A unique monumental complex constructed in the 3rd century b.c. has been identified and is interpreted as a public structure potentially used for ritual activities; the study of this complex raises questions about the creation and reception of markers of civic identity. Excavation data has further characterized the reorganizations that took place during the first centuries a.d., when Gabii's settled area contracted. Rather than unidirectional decline, evidence for industrial activities increases, and elite investments in the city persist, especially in the mixed-use elite domestic and agricultural complex. These results provide detailed evidence for how ancient cities developed and transformed in the face of shifting local and regional conditions, especially smaller urban centers (Gabii) at the periphery of mega-urban centers (Rome).